Nuclear-based combined heat and power industrial energy parks − application of high temperature small modular reactors - Václav Novotný; Junyung Kim; So-Bin Cho; Aidan Rigby; Rami M. Saeed (Energy Conversion and Management: X)
This study identifies industries that are well-suited for replacing or supplementing existing process heating facilities with nuclear power to reduce GHG emissions. Three criteria are considered in selecting target industries: energy demand, applicability of heat from nuclear energy, and the operating principles of the industries. This study also investigates the role of thermal energy storage (TES) in enhancing the integration of nuclear systems within industrial energy parks, exploring its impact on various industrial processes such as chemical plants, oil refineries, and steel production facilities. The novelty of this work lies in its comprehensive examination of TES integration between the nuclear primary loop and the steam cycle, ensuring that system performance is not compromised. This research goes beyond previous efforts by demonstrating the potential for moderate-temperature nuclear heat to replace fossil-based systems in many industries, while highlighting the challenges of meeting high-temperature demands. The study utilized a two-tank molten-salt TES system to provide flexible combined heat and power (CHP) to an industrial energy park, where diverse thermal and electric demands are integrated. A case study shows that TES integration can significantly reduce reliance on natural gas boilers by 9%-77% and decrease dependence on external grids, achieving substantial internal electricity supply. The economic analysis revealed the cost-optimal trade-offs of Nuclear-TES-CHP systems when integrated with existing natural gas boilers in the industrial plant. This study emphasizes the critical role of TES in achieving decarbonization goals, positioning it as an essential element for future industrial energy solutions.